Small-scale poultry: Science-innovation-business - Dessie, Tadelle (International Livestock Research Institute, 2025)
This keynote presentation explores the transformation of small-scale poultry production in sub-Saharan Africa and Southeast Asia through science, innovation, and business-oriented approaches. Drawing on the experience of the Tropical Poultry Genetic Solutions (TPGS) initiative, the session highlights how high-producing, farmer-preferred chicken breeds, combined with robust public-private partnerships and inclusive innovation platforms, are addressing longstanding challenges in the poultry sector. Emphasis is placed on leveraging genetic improvement, empowering women, and integrating poultry production with broader nutrition and livelihood outcomes. The presentation also reflects on lessons learned, the shift to participatory approaches, and the importance of sustainable commercialization for long-term impact. TPGS's work across more than 20 African countries underscores the potential of context-specific, science-based interventions to drive inclusive growth in smallholder poultry value chains.